Can Ethylene Tetra Fluoro Ethylene cushions double skin façade applications improve buildings envelope performance, reduce energy consumption and enhance visual and thermal comfort in UAE buildings? - MANSY, AHMED ABDELAZIZ YOUSSEF (2019)
Innovative façade design technique as a response to the ambient weather conditions has been investigated continuously by building specialists as they have a direct impact on internal conditions and energy consumption in any building. However, the subject of the light weight double skin façade, as a strategic solution to enhance the envelope performance for new and existing buildings, have not been covered sufficiently in our region under the middle east weather conditions. Also, the performance of the ETFE double skin facade is still questionable due to the lack of the experience, recorded data especially in the UAE. The research focused on analysing the impacts of installing ten light weight ETFE double skin façade options on an office building in Abu Dhabi, UAE in order to evaluate these design options as strategic sustainable solutions that can reduced energy consumption and enhance visual and thermal comfort within new or existing buildings. After testing different simulation programs, IES-VE was selected for the study. The software was validated by comparing the basic-model simulation results with the electrical loads calculation that were approved by Abu Dhabi Distribution Company. The ten design scenarios included different passive and active applications and covered changes in the ETFE cushions parameters and the addition of different ceramic frit pattern, two different types of building integrated thin film photovoltaic panels (BIPVs) and ETFE single foil dynamic shades to the system. The final scenario was the optimal option which included all combined design strategies. The analysis of these different options in IES-VE aimed to assess their impact on energy consumption, comfort index, room temperature, people dissatisfaction level, daylighting levels, daylight factor levels, daylight glare index (DGI), Guth visual comfort probability (GVCP) and daylighting harvesting potential. Also, the study included computer fluid dynamics (CFD) to understand changes in temperature and air velocity within the DSF cavity. The results of each scenario were compared with base model/existing building results to evaluate the increment and reduction in each of the studied parameters. The CFD analysis of all scenarios proved that there was a vertical air flow with different rates within the cavity of the corridor DSF which helped to discharge the hot air from the top outlet. The addition of the double layer ETFE cushions as a second envelope layer improved most of the factors with a minor reduction in both daylight factor and daylight illumination levels and managed to reduce energy consumption by 11.594~11.603%. The addition of ETFE layer reduced the total energy consumption by additional 0.85% while maintaining similar thermal comfort analysis results, doubling the reduction of daylighting quality while improving visual comfort. The addition of 30%~60% frit pattern reduced the total annual electricity consumption by additional 0.15% ~ 0.25% with remarkable reduction in people dissatisfied index and DGI. However, it massively reduced the daylighting levels. When the different BIPV types were added, energy consumption was reduced by additional 2% and 4.4% while improving thermal and visual comfort and reducing daylighting quality. The addition of dynamic shades reduced energy consumption by additional 2.2% while having similar impacts on the other factors. The final optimal scenario achieved a total electricity consumption reduction of 19.1% comparing to the basic model with a major improvement in thermal and visual comfort factors. However, these improvements were associated with noticeable reduction in daylighting levels.